2018
DOI: 10.1186/s12889-018-5577-4
|View full text |Cite
|
Sign up to set email alerts
|

Increasing prevalence of overweight and obesity in Yi farmers and migrants from 2007 to 2015 in China: the Yi migrant study

Abstract: BackgroundWith the social development and lifestyle transition, increasing trends of overweight and obesity prevalence are commonly reported worldwide. Data focusing on overweight and obesity trends in rural residents and rural-to-urban migrants in China are limited. This study aims to assess the changes and related factors of overweight and obesity in Yi farmers and migrants in southwest China from 2007 to 2015, and to assess the disparities in prevalence changes.MethodsPseudo-panel data was obtained from two… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
12
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 29 publications
2
12
0
2
Order By: Relevance
“…ey were one of the least developed minority groups in China, which lead an extremely low socioeconomic status. In our previous studies, we found a significant increasing trend of prevalence both in hypertension and in overweight/obesity among Yi people during the past twenty years [14][15][16]. We also illustrated that the rapidly growing prevalence of hypertension in Yi people was primarily due to the parallel increasing mean value of BMI [14].…”
Section: Introductionsupporting
confidence: 56%
“…ey were one of the least developed minority groups in China, which lead an extremely low socioeconomic status. In our previous studies, we found a significant increasing trend of prevalence both in hypertension and in overweight/obesity among Yi people during the past twenty years [14][15][16]. We also illustrated that the rapidly growing prevalence of hypertension in Yi people was primarily due to the parallel increasing mean value of BMI [14].…”
Section: Introductionsupporting
confidence: 56%
“…Details of this survey have been published elsewhere. [ 13 , 14 ] Briefly, a stratified cluster sampling method was used to enroll participants aged 20 to 80 years. In the first stage, Xichang city and Puge county were selected from Liangshan Yi Autonomous Prefecture.…”
Section: Methodsmentioning
confidence: 99%
“…Since the 1950s, some of them began to migrate to urban areas and changed their lifestyle. Disparities in non-communicable diseases risks between Yi farmers and Yi migrants have been described by our previous studies, [ 11 13 ] but the relationship between overweight/obesity and acculturation is still unclear. Therefore, using data from the Yi migrant study, the present study aims to evaluate the risk of overweight/obesity in Yi farmers and rural-to-urban Yi migrants, and further examine the association between age at arrival, duration of migration and overweigh/obesity in Yi migrants.…”
Section: Introductionmentioning
confidence: 97%
“…Since the 1950s, some Yi farmers migrated to urban areas for living and working. Previous work of the Yi Migrant Study has well-demonstrated the effects of rural-to-urban migration on chronic diseases (11)(12)(13). But the relationship between SES and obesity in Yi migrants is not clear, especially existing the fact that the SES varied by acculturation groups in migrants.…”
Section: Introductionmentioning
confidence: 99%